Public Order Policing: A Professional's Guide to International Theories, Case Studies, and Best Practices - Bürger, Bernd; Madensen, Tamara; Lee, Ryan (Springer International Publishing, 2023)
Chapter 1. Public Order Policing. From Theory to Practice -- Chapter 2. Preventing Crime at Assemblies -- Chapter 3. How Collective Violence Emerges and Escalates -- Chapter 4. Interpretive Regimes of Violence in Action. The “Welcome to Hell” Demonstration During the G20 Summit in Hamburg 2017 -- Chapter 5. Almost Forgotten Experiential Knowledge of De-escalation -- Chapter 6. The Role of Police in Assemblies: Ethical Implications, Imperatives, and Interventions -- Chapter 7. Differences in U.S. and German Police Organizations with an Impact on the Policing of Public Assemblies -- Chapter 8. Police Organization and the Policing of Assemblies in Germany -- Chapter 9. Police Organization and the Policing of Assemblies in the United States -- Chapter 10. Protection of Citizens’ Rights, Public Safety & Police Legitimacy - The Legal Equilibrium for Public Order -- Chapter 11. Public Order Policing in the UK -- Chapter 12. Specialized Public Order Units: Integrating a Community Policing Mindset -- Chapter 13. Maintaining Public Order from a Military Police Perspective -- Chapter 14. January 6th – a Challenge for Public Order Policing and Democracy -- Chapter 15. The "Yellow Vest Protests". A Challenge for Police and Democracy -- Chapter 16. Public Order Policing 2.0. Addressing the Challenges of the Information Age -- Chapter 17. Intelligence in Public Order Policing -- Chapter 18. The Importance of Police Public Relations in Assembly Situations -- Chapter 19. Mission Communication as an Integrative Overall Strategy in Protest 2.0 -- Chapter 20. Public Order Standards – Moving the Public Trust Needle Forward -- Chapter 21. Building an Evidence-Based Training Curriculum for Public Order Policing: A Case Study -- Chapter 22. Public Order Policing: Use of Force -- Chapter 23. Considerations for Personal Protective Equipment for Public Order Policing.